Myfinancial controller: a first usability review - Mohamed, Nurul Syahina; Olowolayemo, Akeem; Saliu-Olaojo, Fatimoh Damola; Muhammad, Ibrahim Muhammad (IIUM Press, 2025)
MyFinancial Controller is a mobile application designed to transform the flow of personal finance management and savings in Malaysia. This app helps users to take control of their financial well-being by providing a thorough and user-centric approach to managing and growing personal finances by seamlessly integrating various financial tools and features into a single, intuitive platform. This app offers digital payment solutions, expense analysis, goal-oriented savings and focusing on financial education. MyFinancial Controller caters to diverse and evolving financial needs of users. Notably, MyFinancial Controller includes an advanced Scam Tracker function, which serves as a critical component of the app. This feature provides information about scams and fraudulent activities in the financial sphere, enhancing the security and trustworthiness of the platform. This app equips users with the tools they need to make secure and efficient digital payments, manage expenses, and track their spending. It fosters financial discipline by automating savings, enabling users to establish and customize savings goals, whether for emergencies, dream vacations, or debt management. Moreover, MyFinancial Controller places strong emphasis on financial literacy, providing resources such as articles, tutorials, and interactive tools that enhance users' financial understanding. By serving as a holistic, secure, and innovative personal finance management solution, MyFinancial Controller is at the forefront of reshaping how individuals manage and grow their finances in the dynamic financial landscape of Malaysia